2015
DOI: 10.1007/s10661-015-4265-4
|View full text |Cite
|
Sign up to set email alerts
|

Human health risk assessment via drinking water pathway due to metal contamination in the groundwater of Subarnarekha River Basin, India

Abstract: Groundwater samples were collected from 30 sampling sites throughout the Subarnarekha River Basin for source apportionment and risk assessment studies. The concentrations of As, Ba, Cd, Cr, Co, Cu, Fe, Mn, Mo, Ni, Se, Sr, V and Zn were determined using inductively coupled plasma-mass spectrometry (ICP-MS). The results demonstrated that concentrations of the metals showed significant spatial variation with some of the metals like As, Mn, Fe, Cu and Se exceeding the drinking water standards at some locations. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
71
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(74 citation statements)
references
References 62 publications
2
71
0
1
Order By: Relevance
“…Because groundwater contamination is becoming even more serious than ever before due to fast industrial development and extensive application of fertilizers in agriculture, causing cancers in human body (Zhang et al 2014a), similar health-risk assessment studies have been carried out all over the world (e.g., Cai et al 2015;Giri and Singh 2015;López-Roldán et al 2015;Navoni et al 2014;Wongsasuluk et al 2013;Yang et al 2012). In the present study, a comparison regarding health risk due to groundwater contamination has been made among similar regions in China and the world to provide a better understanding of the health risk in the study area.…”
Section: Health Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…Because groundwater contamination is becoming even more serious than ever before due to fast industrial development and extensive application of fertilizers in agriculture, causing cancers in human body (Zhang et al 2014a), similar health-risk assessment studies have been carried out all over the world (e.g., Cai et al 2015;Giri and Singh 2015;López-Roldán et al 2015;Navoni et al 2014;Wongsasuluk et al 2013;Yang et al 2012). In the present study, a comparison regarding health risk due to groundwater contamination has been made among similar regions in China and the world to provide a better understanding of the health risk in the study area.…”
Section: Health Risksmentioning
confidence: 99%
“…Li and Qian (2011) performed an assessment on drinking water quality and human health risk because of chemical pollutants in groundwater in an industrialized region of China. Similarly, health risk assessment was conducted by Wang et al (2014) and Giri and Singh (2015) independently to examine the adverse impacts of groundwater contaminants on human health. These studies showed that ingestion of the contaminated water was a major pathway of human health risk.…”
Section: Introductionmentioning
confidence: 99%
“…The average daily fish consumption of an adult was 0.0065 kg [24]. The average daily fish consumption of children was 0.0019kg [25]; BCF denoted fish bioaccumulation coefficient (mg/kg/d), where 2.7 for V, 16 for Cr, 47 for Ni, 200 for Cu, 47for Zn, 81for Cd, 49 for Pb [26], and 0.34 for Mn [27]; EF was the exposure frequency (d/a) and the value was 350; ED was the exposure period (a), adult was 30 [28], and child was 6 [29]; Bw was the average body weight (kg), the average adult weight was 56.8, and the average child weight was 15.9; AT was the average time for carcinogenic or non-carcinogenic (d), the average time for carcinogenesis was 25550 [28], the average time for non-cancer in adults was 10950, and the average time for non-carcinogenesis in children was 2190 [29].…”
Section: Human Health Risk Assessmentmentioning
confidence: 99%
“…Scholars have done a lot of research on the potential risks of heavy metals to human health. However, this research concentrated mostly on mining areas [8,9], sewage irrigation [10,11] and waste treatment plants [12,13], with the research subjects focusing on dust reduction [14,15], corn [16,17] , vegetables [18,19], drinking water [20,21], rice [22,23], etc. These studies have carried out in-depth research on the accumulation characteristics, physicochemical properties, occurrence forms and physiological and biochemical effects of contamination by heavy metals, laying a foundation for further research on accumulation of heavy metals in crops and their impact on human health.…”
Section: Introductionmentioning
confidence: 99%